SIMULTANEOUS DETERMINATION OF ALL THE ZEROS OF CHEBYSHEV POLYNOMIAL - Mir, Nazir Ahmad; Akram, Zahida (Journal of Research (Science), 2000)
An algorithm based on modified improved Ehrlich method is developed which finds simultaneously all the zeros of Chebyshev polynomials of first and second kind, the Chebyshev polynomials are generated by a three term recurrence relation. The only information required is degree of the polynomial. The same algorithm works for finding simultaneously all the zeros of real polynomials requiring information about its degree and coefficients.